Comparison of the efficacies of proton pump inhibitors (Lansoprazol and Omeprazol) on Helicobacter pylori eradication - ALADAG Melih KARINCAOGLU Bulent KANTARCEKEN Yuksel SECKIN Ibrahim DOGAN Ayse SERTKAYA Bulent YILDIRIM Fatih HILMIOGLU, Murat (Annals of Medical Research, 2021)
None
Keywords: Helicobacter pylori eradication, clarithromycin, amoxicillin, peptic ulcer, proton pump nh b tors